2007
DOI: 10.1007/bf02897984
|View full text |Cite
|
Sign up to set email alerts
|

Keynote lecture in the 13th Japanese Society of Immunotoxicology (JSIT 2006)

Abstract: Silica and silicates may disturb immune functions such as autoimmunity and tumor immunity, because people who are exposed to the materials sometimes develop autoimmune and malignant diseases, respectively. Although silica-induced disorders of autoimmunity have been explained as adjuvant-type effects of silica, more precise analyses are needed and should reflect the recent progress in immunomolecular findings. A brief summary of our investigations related to the immunological effects of silica/asbestos is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Our previous study showed that the CD4+25+Treg fraction derived from SILs possess impaired regulatory function (24). This reduction in the Treg fraction may be involved in the genesis of autoimmune disturbance found in SILs (8)(9)(10).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous study showed that the CD4+25+Treg fraction derived from SILs possess impaired regulatory function (24). This reduction in the Treg fraction may be involved in the genesis of autoimmune disturbance found in SILs (8)(9)(10).…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported on the cellular and molecular changes associated with Fas and Fasrelated molecules in SILs and healthy donors (HD) (8)(9)(10). Fas is considered to be critical for apoptotic events in immunocompetent cells, such as T cells, and the impairment of Fas through mutation results in excessive autoreaction which causes lymphoproliferative lymphoadenopathy and the occurrence of autoimmune disorders due to the unexpected long-term survival of self-recognizing T cell clones (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation